2021
DOI: 10.23939/tt2021.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of traffic flow intensity on environmental noise pollution

Abstract: The modern urban environment, with the development of industry, the growth of the vehicle's number on the roads, and the increase in the density of buildings, is increasingly capable of negatively affect the health and well-being of the city's population. Among the factors influencing the environment is noise pollution, namely man-made noise - unwanted and harmful sounds created as a result of human activities. Today, noise is one of the most common factors of pollution among all others. The most common source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It is also worth noting that these results are obtained for a traffic flow where buses make up only 3.6 % of the total traffic volume. Also, in the analyzed studies, some results indicated a significant influence of the road surface and the volume of the traffic flow on the noise level of sections of arterial streets [6]. The traffic flow moving on a cobblestone road surface was determined to generate a 20 dBA higher noise level than asphalt concrete (70 vs. 50 dBA).…”
Section: Research Statementmentioning
confidence: 94%
“…It is also worth noting that these results are obtained for a traffic flow where buses make up only 3.6 % of the total traffic volume. Also, in the analyzed studies, some results indicated a significant influence of the road surface and the volume of the traffic flow on the noise level of sections of arterial streets [6]. The traffic flow moving on a cobblestone road surface was determined to generate a 20 dBA higher noise level than asphalt concrete (70 vs. 50 dBA).…”
Section: Research Statementmentioning
confidence: 94%